China Economic Update, June 2021 : Beyond the Recovery - Charting a Green and Inclusive Growth Path - World Bank (World Bank, Washington, DC, 2021)
China’s recovery has broadened as economic activity has continued to normalize. Economic growth in China is projected to reach 8.5 percent this year before slowing to 5.4 percent in 2022, as low base effects dissipate and the economy returns to trend growth. As China’s recovery firms up, macroeconomic policies are expected to shift from accommodative to more neutral settings. The pace of policy normalization, however, should continue to be data-dependent and calibrated to the strength of the recovery in China and the rest of the world. Rising financial vulnerabilities, together with subdued productivity growth and persistent imbalances in the structure of aggregate demand, pose medium-term challenges that require attention. Macroeconomic policies and structural reforms should aim at reinvigorating the shift to more balanced high-quality growth.